Phenethyl Esters and Amide of Ferulic Acid, Hydroferulic Acid, Homovanillic Acid, and Vanillic Acid: Synthesis, Free Radicals Scavenging Activity, and Molecular Modeling as Potential Cholinesterases Inhibitors - Ayyoub Selka; Fanta J. Ndongou Moutombi; Marc Cormier; Mohamed Touaibia (Molbank, 2020)
As ferulic acid was reported to be involved in novel potential mechanisms associated with Alzheimer’s disease (AD) therapy, five closely related phenethyl esters and amide of this natural product were synthesized and screened for their free radicals scavenging activity. Ferulic acid and its analogue′s absorption, distribution, metabolism, and excretion (ADME) properties were predicted. All compounds obey Lipinski′s rules. Moreover, all evaluated compounds seem to present a high oral bioavailability and blood–brain barrier (BBB) permeation which is crucial for Alzheimer′s disease drug candidates. Molecular docking of analogues 4 and 8 with acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) showed interactions with the residues of the catalytic triad of AChE and BChE. In addition to their interactions with the anionic subsite, hydroferulic acid phenethyl ester 4 and homovanillic acid phenethyl ester 8 may have potential as inhibitors of AChE and BChE, respectively.